2002
DOI: 10.1161/01.hyp.0000016400.21001.05
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Dietary Lard-Induced Increase in Blood Pressure in Rats

Abstract: Abstract-We investigated the difference between male and female rats in the increase in blood pressure (BP) when they were fed a lard-enriched diet. We also investigated the effect of a gonadectomy, with or without testosterone treatment, on the dietary lard-induced increase in BP. Wistar-strain male or female rats were bilaterally castrated or ovariectomized. Some of them were implanted subcutaneously with silicon tubes containing crystalline testosterone. Each group was fed either chow alone or chow in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
1
19
3
Order By: Relevance
“…This may imply an irreversible, adverse effect of the maternal diet on pathways of blood pressure control. Others have shown that male Wistar rats fed lard develop raised blood pressure, 25 and it is possible that blood pressure would have been raised further if the animals had not experienced developmental exposure to the diet. Nonetheless, the females were not adapted in early life to remain normotensive when maintained on the same diet as fed to their dams.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply an irreversible, adverse effect of the maternal diet on pathways of blood pressure control. Others have shown that male Wistar rats fed lard develop raised blood pressure, 25 and it is possible that blood pressure would have been raised further if the animals had not experienced developmental exposure to the diet. Nonetheless, the females were not adapted in early life to remain normotensive when maintained on the same diet as fed to their dams.…”
Section: Discussionmentioning
confidence: 99%
“…SFA were reported to increase systolic blood pressure in male rats, but not in female or gonadectomized male rats. 11 Interestingly, this sensitivity to SFA was restored in castrated male rats given testosterone. On the contrary, feeding a diet rich in lard to pregnant rats also affected systolic blood pressure in adult offspring, even if fed a normal diet, but the female offspring were more sensitive than the male to this foetal nutrition-induced hypertension.…”
Section: Hypertension and Sfamentioning
confidence: 96%
“…11 Most of these work in animals, as well as all the investigations in humans, reported in fact the effects of high fat diets making it difficult to distinguish the consequence of lipid excess from the specific effects of SFA. SFA were reported to increase systolic blood pressure in male rats, but not in female or gonadectomized male rats.…”
Section: Hypertension and Sfamentioning
confidence: 99%
“…According to this concept, when postnatal diet is similar to dam's diet, the offspring is protected from the development of disease in adulthood. 124,125 For instance, when high-fat diet persists during postnatal period, the offspring from obese mice does not develop endothelial dysfunction. 124 In contrast, when fat-rich diet is given only during pregnancy and lactation, offspring exhibit reduced aortic endothelium-dependent vasodilatation and increased aortic stiffness.…”
Section: 100mentioning
confidence: 99%